Atomic-scale insight into thermal decomposition behavior of polypropylene: A ReaxFF method. (August 2022) - Guo, Wei; Fan, Kang; Guo, Guanlun; Wang, Jing
Highlights: The ReaxFF MD was implemented on a large PP system. Thermal decomposition behavior of PP was investigated on the atomic scale. Both heating and constant temperature stages were taken into consideration. Both random scission of polymer links and chain-end scission mechanisms played a role in the thermal decomposition of PP. The results of pyrolysis kinetics from simulation were in good agreement with the previous work. Abstract: In this study, reactive force field molecular dynamics (ReaxFF MD) was implemented for the first time on a large polypropylene (PP) system, thermal decomposition characteristics of polypropylene (PP) during both heating and constant temperature process were investigated, and the pyrolysis mechanisms of PP were discussed. At the beginning of the reaction, random C-C bond scission of long PP chains resulted in the formation of a full range of products. In the heating stage, with the increase of the temperature, the product composition gradually shifted to light components and the number of propylene was significantly higher than that of other products. In the constant temperature stage, the long-term high temperature led to the secondary reactions in the system, and the content of heavier components increased. The observation of two partial reaction pathways indicated that both random scission of polymer links and chain-end scission mechanisms played a role in the thermal decomposition of PP. The analysis of pyrolysis kinetics based on simulation data suggested that the Contracting Cylinder model would be suitable for PP pyrolysis, and the activation energy for overall degradation of PP was in good agreement with the previous work. The current results would be helpful in illustrating the pyrolysis processes of PP and understanding its reaction mechanisms.